Pemanfaatan Media Sosial untuk Mendukung Kegiatan Penyuluhan Pertanian di Kabupaten Minahasa Provinsi Sulawesi Utara - Suratini Suratini; Pudji Muljono; Cahyono Tri Wibowo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2021)
The rapid development of communication technology requires agricultural extension workers to be able to use social media in disseminating agricultural information. This study aims to describe the use of social media, analyze the factors associated with the level of social media utilization and analyze the management of agricultural information and its relationship with the use of social media. The study used the observation method to select respondents through the census.The level of social media utilization by respondents was measured by the frequency and duration in using Facebook, WhatsApp, Youtube and Instagram . The frequency of using social media is relatively high for Facebook and WhatsApp. The overall duration of accessing social media is relatively low. Factors that are significantly related to the utilization level of social media are the characteristics of extension workers (level of education and the availability of communication technology tools), perception of extension workers (ease of acces to information), information needs of extension workers (climate and capital) and motivation of extension workers (increasing knowledge and insight). Almost all extension workers manage information obtained from social media to be distributed to farmers.